2020
DOI: 10.1103/physrevb.102.214111
|View full text |Cite
|
Sign up to set email alerts
|

Contrast reversal in atomic-scale phonon spectroscopic imaging

Abstract: This is a repository copy of Contrast reversal in atomic-scale phonon spectroscopic imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…The magnon signal of the BF detector shows expected strong dynamical diffraction effects with volcano-shaped features around the atomic columns. A similar behavior was reported in phonon EELS maps [30]. The contrast is lower with a ratio of maximal to minimal intensities near a factor of 5, while the relative strength of the magnon signal remains below 10 −6 , at a similar level to the magnon signal collected by the HAADF detector.…”
supporting
confidence: 80%
“…The magnon signal of the BF detector shows expected strong dynamical diffraction effects with volcano-shaped features around the atomic columns. A similar behavior was reported in phonon EELS maps [30]. The contrast is lower with a ratio of maximal to minimal intensities near a factor of 5, while the relative strength of the magnon signal remains below 10 −6 , at a similar level to the magnon signal collected by the HAADF detector.…”
supporting
confidence: 80%
“…So far, two-dimensional (2D) mapping of surface and bulk excitations 23 and detection of single-atom 24 and defect 25 vibrational signals have been achieved. Although dipole scattering in polar materials, such as BN 21 , 26 , 27 , MgO 23 and SiC 20 , 28 , under on-axis scanning transmission electron microscopy-electron energy loss spectroscopy (STEM-EELS) the geometry produces long-range and non-local polariton modes, reducing the atomic-scale contrast in vibrational EELS signal mapping 29 , dipole scattered signals are substantially suppressed and negligible in elemental and non-polar materials with weak dipoles, such as Si 22 and SiGe, which only contain highly localized phonon scattering. Here, we report quantitative high spatial resolution mapping of phonons in SiGe QDs using an on-axis beam-detector geometry (Extended Data Fig.…”
Section: Mainmentioning
confidence: 99%
“…The variation of vibrational signal in the line scan (Extended Data Fig. 8b ) presumably arises from the short-range coulomb interaction between the beam and the atomic nucleus, providing atomic-scale contrast 29 . Interestingly, even when the maximum peak heights are normalized to 1, the Ge OM still shows a strong modulation.…”
Section: Mainmentioning
confidence: 99%
“…The possibility of atomic-resolution phonon mapping was proposed (Lugg et al, 2015 a ; Dwyer, 2017; Hage et al, 2019) and practically realized by Venkatraman et al (2019) (Fig. 8), although the fundamental localization mechanisms and image contrast still need to be carefully evaluated (Hage et al, 2020 b ; Rez & Singh, 2021). Hage et al (2020 a ) demonstrated the detection of distinctive localized vibrational signatures from a single-atom impurity in a solid (Si atom in graphene), clearly demonstrating single-atom sensitivity by STEM vibrational spectroscopy and inviting intriguing implications across the fields of physics, chemistry, and materials science.…”
Section: Development Of the Scanning Transmission Electron Microscopementioning
confidence: 99%